Dependency Rates and Private Savings Behavior in Developing Countries. (IMF Working Papers; Working Paper, 1988)
A firm theoretical basis for the empirical relationship between dependency rates and savings behavior in developing countries is still lacking. Two demographic extensions of the representative household's stochastic dynamic optimization problem are presented here. It is shown that the relationship between expected dependency rates and consumption growth depends on two parameters: the demographically varying committed consumption and the intertemporal elasticity of substitution. Thus, the expected path of demographic variables can provide information on the consumers' willingness to smooth consumption, and on the savings responsiveness to changes in the real interest rate.